THE INFLUENCE OF PRODUCT QUALITY, PRICE AND PROMOTION ON LE MINERALE BRAND DRINKING WATER - Fadila Hardika Putri; Mohamad Trio Febriyantoro; Zulkifli Zulkifli; Dede Suleman; Fendi Saputra; Totok Suyoto (AGUSPATI Research Institute, 2022)
This study aims to determine the effect of product quality, price, and promotion on purchasing decisions of Le Minerale brand bottled drinking water). This type of research is quantitative research. The subjects of this research are consumers who buy Le Minerale products. Primary data was obtained from a questionnaire with 108 respondents using the Google form. Then the collected data will be analyzed using multiple linear regression with the help of SPSS 23. The results of this study can be concluded based on the t test that each variable is product quality (X¹), price (X²), and promotion (X³) have a positive and significant effect, thus influencing the purchasing decision (Y)